Strategi Pengelolaan Sumber Daya Manusia dalam Meningkatkan Kinerja Berkelanjutan Di Rumah Sakit Tipe C Jakarta Timur - Dicky Yulius Pangkey; Masydzulhak Djamil; Ahmad Hidayat Sutawijaya; Ahmad Badawi Saluy (Universitas Mercu Buana, 2022)
Hospitals are an essential part of the health sector; this makes the hospital service industry important. Facing increasingly fierce competition in health care services, every hospital requires proper and good management without reducing the quality of service. Not only applying the concept of good quality human resources, but every employee of the hospital service industry can carry out the vision and mission that is supported by management strategies that can not only improve performance but are also sustainable. Pre-survey was conducted to find out what factors can improve sustainable performance. Three hospitals type C in East Jakarta became the pre-survey research population, based on performance data it was found that the three hospitals were only able to achieve 80 percent performance, with leadership, loyalty, and initiative scores having quite low proportions. A total of 60 employees participated in the pre-survey. Pre-survey results show that employees have a low organizational commitment (3.65) and believe that they have sufficient competence (4.36) which is expected of the hospital where they work. These results indicate that sustainable performance needs to be investigated further, especially what factors can influence it. The implications for further research are explained in the discussion.